HUBUNGAN PERAN EDUCATOR PERAWAT DALAM DISCHARGE PLANNING DENGAN TINGKAT KEPATUHAN PASIEN RAWAT INAP UNTUK KONTROL DI RUMAH SAKIT GRANDMED LUBUK PAKAM TAHUN 2021 - Pitriani .; Samuel Ginting; Dian Anggri Yanti; Juni Mariati Simarmata; Arfah May Syara; Rita Ayu Butar Butar (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2021)
The role of educators is to help patients improve their health by providing knowledge about medical treatments and actions received so that patients or families can find out important knowledge for patients or their families. The research objective was to analyze the relationship between the role of the nurse educator in discharge planning with the level of compliance of inpatients for control at Grandmed Lubuk Pakam Hospital. The research method is this research using analytic observational research using a cross sectional study. In a study with a cross sectional study, measurement and data collection were carried out on the cause and effect variables for a moment at a time. The results of the research in this study The statistical test results showed the value of p = 0.001. Ha is accepted if Ho is rejected, where Ho is rejected if the p value is â‰¤ Î±, 0.001 â‰¤ 0.05. The results of statistical analysis showed that there was a significant relationship between the role of nurse educators in discharge planning and the level of inpatient compliance for control. Conclusion: The role of nurse educators in discharge planning was in the good category, namely 23 people, the level of patient adherence to control was 24 people (60%).